Double layer graft technique for horizontal alveolar ridge augmentation with staged implant placement: radiographic histological and implant stability analysis-a case report - Leila Elraee; Suzan Seif Allah Ibrahim; Doaa Adel-Khattab (BMC, 2024)
Abstract Introduction Horizontal ridge augmentation of a deficient alveolar bone site is performed either simultaneously with implant placement or in a staged approach prior to implant insertion. There are several available strategies for the augmentation of alveolar ridge deficiencies, including guided bone regeneration (GBR) through the use of barrier membranes. The success of the GBR approach mainly depends on the exclusion of soft tissue cells during bone remodeling. Case presentation A healthy 25-year-old male patient presented with a missing upper left central incisor after clinical and radiographic examination, the site showed a class III defect horizontal atrophy. The procedure performed was the horizontal alveolar ridge augmentation using resorbable pericardium membrane with double layer graft technique (DLT) where autogenous bone placed as a first layer of the graft followed by xenograft as a second layer, the membrane was fixed with titanium pins. A cone beam computed tomography (CBCT) was performed before, immediately and 6 month following the surgery. After 6 months during implant placement, a core biopsy specimen was retrieved, stored and prepared for histological evaluation, with assessment of primary implant stability. The radiographic analysis showed a horizontal width gain of about 4 mm, at 6 month following implant placement, the implant was successfully osteointegrated with stability assessment also done after 6 months from placement. Conclusion DLT was successfully used for horizontal alveolar ridge augmentation, thus allowing a prosthetically driven implant placement. More cases assessing implant survival and success are needed to confirm the results of this case report.